2004
DOI: 10.2337/diabetes.53.6.1418
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Recruitment Is an Early Insulin Effect That Regulates Skeletal Muscle Glucose Uptake In Vivo

Abstract: Insulin increases glucose disposal into muscle. In addition, in vivo insulin elicits distinct nitric oxide synthase-dependent vascular responses to increase total skeletal muscle blood flow and to recruit muscle capillaries (by relaxing resistance and terminal arterioles, respectively). In the current study, we compared the temporal sequence of vascular and metabolic responses to a 30-min physiological infusion of insulin (3 mU ⅐ min ؊1 ⅐ kg ؊1 , euglycemic clamp) or saline in rat skeletal muscle in vivo. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
485
5
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 378 publications
(518 citation statements)
references
References 40 publications
23
485
5
5
Order By: Relevance
“…However, in the present studies, the heart rate and blood pressure were normal and other recent studies have shown that insulin-mediated capillary recruitment occurred early, relative to muscle glucose uptake [18] and at physiological doses of insulin [17], indicating that a desensitising effect of the anaesthetic is unlikely. Moreover, studies in human forearm, where the subjects were instructed to remain still, have shown insulin-mediated capillary recruitment, again at physiological insulin levels [44].…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…However, in the present studies, the heart rate and blood pressure were normal and other recent studies have shown that insulin-mediated capillary recruitment occurred early, relative to muscle glucose uptake [18] and at physiological doses of insulin [17], indicating that a desensitising effect of the anaesthetic is unlikely. Moreover, studies in human forearm, where the subjects were instructed to remain still, have shown insulin-mediated capillary recruitment, again at physiological insulin levels [44].…”
Section: Discussioncontrasting
confidence: 59%
“…However, there is now indirect evidence making it unlikely that insulinmediated capillary recruitment is regulated by metabolite(s) from muscle. Thus insulin-mediated capillary recruitment, measured by contrast-enhanced ultrasound, is an early event in insulin action in vivo preceding the stimulation of glucose uptake [18]. We have also shown, using both 1-MX metabolism and contrast-enhanced ultrasound, that capillary recruitment occurs at insulin concentrations that do not alter muscle glucose uptake [17].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations